Hypercalcemia and acute pancreatitis in a male patient with acute promyelocytic leukemia and pulmonary tuberculosis - Abdullah, Ali S; Adel, Ahmad M; Hussein, Radwa M; Abdullah, Mohammed AJ; Yousaf, Anil; Mudawi, Deena; Mohamed, Shehab F; Nashwan, Abdulqadir J; Soliman, Dina; Ibrahim, Feryal; Yassin, Mohamed A (Acta Biomedica Atenei Parmensis, 2018)
We report a rare case of hypercalcemia and acute pancreatitis in a subject with acute promyelocytic leukemia (APL) and pulmonary tuberculosis, during all-trans-retinoic acid (ATRA) treatment. Both associated complications were potentially due to several causes. A careful monitoring and exclusion of all causative factors must be addressed. Further research is necessary to improve our understanding of risk factors for these complications in patients with (APL). Studying these patterns may help us to improve outcomes for all children and young adults with hematologic malignancies